Jurnal Vokasi ANALISIS LEMBAGA KEUANGAN MIKRO SYARIAH BERBASIS WAKAF: KAJIAN LITERATUR: Akuntansi Lembaga Keuangan Syariah - Pupun Saepul Rohman; Ai Yani (Politeknik Bisnis Mayasari, 2022)
Analysis of Waqf-Based Islamic Microfinance Institutions: Literature Review. The purpose of this study was to analyze the literature related to waqf-based Islamic microfinance institutions. The method used is a literature review, namely by collecting and analyzing a collection of Islamic microfinance articles from international journals and other reputable journals. The results show that Islamic microfinance institutions have the potential to be a solution for the availability of financial institutions that are free from usury transactions. In addition, this institution also has the potential to become an empowerment tool.